Consumer-brand engagement on Instagram - Mendes, José Alexandre Feliciano (2019)
Social media has been subject to an increasing number of studies. Although there is empirical research on consumer–brand interaction on social media, such as on Facebook, there is still a lack of studies on other SNS. As a marketing tool that allows brands to connect and engage with their consumers, Instagram is pointed out as a critical social network. However, there is still a lack of marketing studies on consumer-brand engagement on Instagram. Therefore, the purpose of this research is to understand the motivations for consumer to engage with a brand through Instagram. The findings should provide brand managers guidelines to develop a more effective strategy to approach this SNS. In order to fulfill the research purpose, we used an online survey with 177 valid responses. To understand the relationship between consumer motivations and consumer-brand engagement on Instagram, a multiple linear regression was performed. The results indicate that the main motivation to consume brand content on Instagram is search for information. The main motivations to actively interact with brand related content are social influence and personal identity. Brands that seek to attract their consumers to their Instagram page should offer convenient access to information, by creating interesting content through short stories, videos or photos, they should also stimulate users to share their opinion and offer appealing prizes and discounts. Further research could apply this study to a specific brand or product category.